2022
DOI: 10.1371/journal.pone.0277675
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and effect of universal test-and-treat on twelve months retention and initial virologic suppression in routine HIV program in Kenya

Abstract: Early combination antiretroviral therapy (cART), as recommended in WHO’s universal test-and-treat (UTT) policy, is associated with improved linkage to care, retention, and virologic suppression in controlled studies. We aimed to describe UTT uptake and effect on twelve-month non-retention and initial virologic non-suppression (VnS) among HIV infected adults starting cART in routine HIV program in Kenya. Individual-level HIV service delivery data from 38 health facilities, each representing 38 of the 47 countie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Utilising the denominator of those with viral load results available, over 90% of all three groups were virally suppressed, which is higher than Kenya national programme data (85% virally suppressed among those with available viral load results. 25 A study evaluating national programme data from Kenya showed that male individuals were half as likely to get a viral test compared with female individuals. 26 The incomplete assessment of viral load adds uncertainty to our results; however, male individuals with newly diagnosed HIV also have slightly lower confirmed retention on ART at 12 months (86%) compared with male individuals with known HIV-positive status (90%) and female individuals (88%) at 12 months, and retention in care declined in all groups over time.…”
Section: Discussionmentioning
confidence: 99%
“…Utilising the denominator of those with viral load results available, over 90% of all three groups were virally suppressed, which is higher than Kenya national programme data (85% virally suppressed among those with available viral load results. 25 A study evaluating national programme data from Kenya showed that male individuals were half as likely to get a viral test compared with female individuals. 26 The incomplete assessment of viral load adds uncertainty to our results; however, male individuals with newly diagnosed HIV also have slightly lower confirmed retention on ART at 12 months (86%) compared with male individuals with known HIV-positive status (90%) and female individuals (88%) at 12 months, and retention in care declined in all groups over time.…”
Section: Discussionmentioning
confidence: 99%
“…This sharp increase from 2016 corresponded with the introduction of the test and treat-all strategy. Substantial uptake of the UTT policy has been reported across several sub-Saharan African countries [ [20] , [21] , [22] , [23] , [24] , [25] ]. This successful implementation of the UTT policy has been facilitated intuitively from the removal of the CD4 eligibility threshold for ART initiation, but also by experiences gained from the Option B+ approach that preceded UTT, the extraordinary financial support and pressures from different stakeholders (from governments, civil society groups, researchers, and donors) to accelerate the implementation of UTT [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Cox regression model was used to screen for factors independently associated with VLS or VLR. These factors were selected based on a previous study in Kenya by Kimanga et al [ 16 ]. Hazard ratios with their corresponding 95% confidence intervals (95%CI) and p-values were obtained from the final multivariable Cox model.…”
Section: Methodsmentioning
confidence: 99%